Cream Formulation of Ampelas Twig Extract (Tetracera macrophylla Wall. Ex Hook.f. & Thomson) as a Wound Healer - Vera Ladeska; Trisantia Nabela; Kriana Efendi (Jurnal FARMASIMED (JFM), 2026)
The island of Kalimantan is where the native Indonesian plant known as ampelas originated. The twigs of this plant offer a variety of pharmacological properties, including the ability to treat fever, gout, and diabetes, according to scientific and empirical research. In order to assess the anti-inflammatory properties of ampelas twig ethyl acetate extract in the healing phase of open wounds, this study was conducted. A cream containing ethyl acetate extract of ampelas twigs at concentrations of 2%, 4%, and 6% was applied to the wounds of male Wistar strain white rats in five groups: group I was the negative control, group II was the positive control hydrocortisone 2.5 percent, and groups III, IV, and V were the test animal models. Until the fourteenth day, the rats' backs were shaved, wounds were formed to the dermis layer, and the wounds were treated and monitored for shrinking. ANOVA statistical analysis revealed that the proportion of open wound healing varied significantly between test groups. The Tukey test revealed that ampelas twig ethyl acetate extract at a concentration of 6% could heal wounds on par with the positive control. For all test groups, the best time to heal open wounds was on day 14.